(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The development of hydrogen energy in the context of the global energy transition is a strategic goal formulated by the Government of the Russian Federation in the approved regulation "The Concept of Development of Hydrogen Energy in the Russian Federation". The development of hydrogen transport, the production and use of hydrogen in various industries, as well as the development of fuel cell storage technology, have as a priority area. Despite the problems that affect the development of hydrogen fuel infrastructure in Russia, namely, high cost, low domestic demand for hydrogen, and insufficient technology competitiveness, there are also significant strategic advantages. These include significant energy resources, including fossil fuels, cheap electricity, hydro and nuclear power, a well-developed gas transportation structure and a high technological level.